Photodetectors: Broadband High‐Responsivity Photodetectors Based on Large‐Scale Topological Crystalline Insulator SnTe Ultrathin Film Grown by Molecular Beam Epitaxy (Advanced Optical Materials 5/2017). Issue 5 (March 2017) - Jiang, Tian; Zang, Yunyi; Sun, Honghui; Zheng, Xin; Liu, Yu; Gong, Yan; Fang, Liang; Cheng, Xiang'ai; He, Ke
Abstract : Broadband high responsivity photodetectors based on large scale topological crystalline insulator SnTe ultrathin film grown by molecular beam epitaxy are fabricated by Tian Jiang, Xiang'ai Cheng, and co‐workers in article number 1600727. The photoconductive detectors exhibit fast and stable photoresponses from the visible to mid‐infrared range (405 nm−3.8 μm) and high responsibility (3.75 AW −1 at 2003 nm at room temperature), which will promote applications in broadband and sensitive optoelectronic devices.